O discurso e a ação : análise do processo de mudança no sistema de controle gerencial em uma organização industrial brasileira sob a ótica da teoria institucional - Bubach, Célia (2015)
The aim of this study was to investigate the process of change in management control system (MCS), analyzing the change of management control practices in the structure of this system, from the perspective of institutional theory. The research question is